Pengaplikasian Qris Pada Menu Restaurant Dan Pembayaran Melalui Barcode Berbasis Web - Saryani Saryani (Universitas Tangerang Raya, 2026)
The development of information technology has driven innovation in digital payment systems, one of which is through the implementation of QRIS (Quick Response Code Indonesian Standard) issued by Bank Indonesia. This study aims to implement a digital system through the use of QR codes, so customers can order directly from the table without having to queue. This digital system was created to simplify the customer ordering and transaction process. The designed solution includes the development of a website application that displays the menu and allows online ordering, integrated with the Point of Sale (POS) system through an API. The system development method uses the waterfall model, including the stages of needs analysis, system design, implementation, and testing. Through this system digitization, customers can scan the QR code at each table to access the menu, order, and make payments. Test results show that the system can run well on various devices and is able to increase transaction efficiency, reduce queues, and minimize errors in recording orders and payments. Thus, the implementation of QRIS in a web-based restaurant menu system has proven effective in supporting the digitalization of transactions and services in the culinary sector.